TERC polymorphisms are associated both with susceptibility to colorectal cancer and with longer telomeres. Issue 2 (27th June 2011) - Jones, A M; Beggs, A D; Carvajal-Carmona, L; Farrington, S; Tenesa, A; Walker, M; Howarth, K; Ballereau, S; Hodgson, S V; Zauber, A; Bertagnolli, M; Midgley, R; et al.
Abstract : Background and aims: Shorter telomeres have been associated with increased risk of malignancy, including colorectal cancer (CRC). Telomere length is heritable and may be an intermediate phenotype linked to genetic susceptibility to CRC. Methods: In a large sample, the study investigated whether candidate single nucleotide polymorphisms (SNP) in 'telomere biology' genes were associated with telomere length in leucocytes. SNP associated with an increased risk of CRC were searched for separately. Results: Carriers of the common allele at SNP rs10936599, near the telomerase RNA component (TERC) locus, had significantly longer telomeres. It was independently found that the same rs10936599 allele was associated with increased risk of both CRC and colorectal adenomas. Neither telomere length nor CRC risk was associated with variation near telomerase reverse transcriptase or other telomere biology genes. In silico analysis showed that SNP rs2293607 was strongly correlated with rs10936599, mapped within TERC transcripts, had a predicted effect on messenger RNA folding and lay at a reported transcription factor binding site. TERC mRNA were expressed, differing only at the alleles of rs2293607, in CRC cell line HCT116. The long-telomere/CRC-risk allele was associated with higher levels of TERC mRNA and the formation of longer telomeres. Conclusions: Common genetic variation at TERC is associated with both longer telomeres and an increased risk of CRC, a potential mechanism being reduced levels of cell senescence or death. This finding is somewhat paradoxical, given retrospective studies reporting that CRC cases have shorter telomeres than controls. One possibility is that that association actually results from poorer survival in patients with longer telomeres.